Sosialisasi Alat Peraga Matematika Bagi Guru SD Negeri Krueng Baung - Nurdiana Nurdiana (Institut Teknologi dan Bisnis Semarang, 2023)
This community service aims to provide media training or mathematics-based teaching aids for Krueng Baung State Elementary School teachers located in Peunaron Lama Village, Peunaron District, Aceh. The methods we use are the question and answer method and the skills method. Socialization or meetings start and end on May 11 2020 at 08.00. This event is a social event and takes place in one session only. The problem that occurs in schools is that students are not very interested in learning mathematics because learning is considered very difficult. Having mathematics learning props will make it easier for students to understand mathematics, where students can find it easier to find multiplication results or the correct answer, it will also encourage them to be able to count and teachers will make it easier for them to convey the material without feeling difficult. The teaching aids used are easier and easier for students to understand, so students will feel that learning is easier and easier to understand because of the help of these learning media. By using this teaching aid, the principal agrees to explain this media because it is easy and appropriate for elementary school children to make it easier for them to do multiplication.